Ni adsorption by similar Structured Brown Earth and by Red-Yellow Podzolic soil - Pombo, Leda; Salgado, Valnita; Volkweiss, Sergio; Klamt, Egon (Pesquisa Agropecuaria Brasileira, 2014)
Ni is considered an ambiental polutant and when present in excess causes toxicity to plants as well as to animals that ingest them. The objective of this work is to study Ni adsorption by two Ultlisols: a Structured Brown Earth - SBE (Carlos Barbosa Unit) and Red-Yellow Podzolic (RYP) soil (Bom Retiro Unit), verifying the applicability of the Langmuir equation and testing the effect of pH on its availability. The adsorption tests were carried out on soil surface samples under different values of pH and with increasing concentrations of Ni in solution. Desorption was performed with CH3COONH4 1 N pH 7,0 in samples of both soils and in samples of the RYP soil, whose pH was elevated to 5.3 e 5.5 by liming, respectively with CaCl2 1 M and HCl 0.01 N. In both soils the Ni adsorption can be represented by the Langmuir equation; in extraction solutions of both soils, Mg increased and K decreased with the increasing of pH by liming. The amount of Ni to be applied to both soils depends on the level of pH to be attained by liming being the recommended pH about 6,0. The amounts of Ni desorbed with CH3COONH4 1 N pH 7.0 to both soils and with CaCl2 1 M to RYP soil whose pH was elevated to 5.3 were small, but the amounts of Ni desorbed with HCl 0,01 M to the RYP soil with pH 5,5, were elevated.